2020
DOI: 10.1017/s0266462320002159
|View full text |Cite
|
Sign up to set email alerts
|

Creating enriched training sets of eligible studies for large systematic reviews: the utility of PubMed's Best Match algorithm

Abstract: Introduction Solutions like crowd screening and machine learning can assist systematic reviewers with heavy screening burdens but require training sets containing a mix of eligible and ineligible studies. This study explores using PubMed's Best Match algorithm to create small training sets containing at least five relevant studies. Methods Six systematic reviews were examined retrospectively. MEDLINE searches were converted and run in PubMed. The ranking of included studies was studied u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…We would like to compare search results in Best Match between expert searchers and nonexpert searchers such as students, doctors, and clinical researchers by asking each group to run a search on a query and observing how they search, determine relevance, and select articles to read. Previously, Sampson performed a study in which she used Best Match as a ranker for results from a systematic review search and found that Best Match sort order “placed three times as many relevant records in the top fifty than Most Recent” results [ 29 ]. However, her study used searches designed by expert searchers.…”
Section: Next Stepsmentioning
confidence: 99%
“…We would like to compare search results in Best Match between expert searchers and nonexpert searchers such as students, doctors, and clinical researchers by asking each group to run a search on a query and observing how they search, determine relevance, and select articles to read. Previously, Sampson performed a study in which she used Best Match as a ranker for results from a systematic review search and found that Best Match sort order “placed three times as many relevant records in the top fifty than Most Recent” results [ 29 ]. However, her study used searches designed by expert searchers.…”
Section: Next Stepsmentioning
confidence: 99%
“…(It is no longer true that retrieved sets are not ranked. In 2019, "best match" replaced "most recent" as the default sort order for search results in PubMed, cf., [21,22]).…”
Section: Challenges From Irmentioning
confidence: 99%
“…This issue also contains a timely methodological evaluation of new database features -the PubMed "Best Match" sorting option evaluated by Sampson et al (9). This is a good example of the methodological support offered by information specialists: new database features or techniques are evaluated and can then be applied according to the evidence.…”
mentioning
confidence: 99%